Characteristics of atmospheric mercury at a suburban site in northern Taiwan and influence of trans-boundary haze events. (1st October 2019) - Sheu, Guey-Rong; Phu Nguyen, Ly Sy; Truong, Minh Tri; Lin, Da-Wei
Abstract: Concentrations of gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), and particle-bound mercury (PBM) were measured at a suburban site in northern Taiwan between October 2017 and September 2018. Mean concentrations of GEM, GOM, and PBM were 2.61 ± 6.47 ng m −3, 12.1 ± 34.3 pg m −3, and 18.7 ± 86.8 pg m −3, respectively. On 35% of the days, elevated atmospheric mercury (Hg) concentration occurred between midnight and early morning when local wind direction shifted and came from sectors between SSW and S, indicating influence of local anthropogenic emission sources. As such, a diurnal pattern with nighttime peaks was observed for GEM, GOM, and PBM. However, elevated GOM values were also observed around noon on 87 occasions, coinciding with peak O3 and solar radiation, suggesting additional contribution from in situ photochemical reactions. Seasonally, atmospheric Hg concentrations were higher in spring than in the other seasons. Besides the contribution from local emissions and the East Asian outflow, lower wind speed, cumulative rainfall, and days of rain in spring suggesting poor air dispersion and inefficient pollutant removal, hence leading to the accumulation of atmospheric Hg and thus higher concentrations. Two trans-boundary haze events from China were encountered during this study. Concentrations of GEM and PBM were enhanced on haze days, with particularly significant enhancement in PBM. Comparison of the maximum PBM values during these haze events to respective pre-event PBM values showed enhancements of 378% and 1438%, whereas enhancements of 100% and 147% were observed for GEM. GOM remained relatively low and stable during haze events, which could be due to the favored partitioning of GOM toward solid phase under high PM2.5 concentrations and the lack of sunlight to fuel the photochemical production of GOM. Backward trajectories indicated that Hg emissions in east China likely contributed to the enhancements in atmospheric Hg concentrations measured at the suburban site in northern Taiwan during these two trans-boundary haze events. Highlights: Both local sources and regional transport contributed to the measured atmospheric Hg. Two trans-boundary haze events from China were encountered. Concentrations of GEM and PBM were enhanced on haze days, but GOM remained low. Yangtze River Delta and east China were the Hg source regions for these haze events.